Does Size Matter in Laryngology? Relation Between Body Height and Laryngeal Morphometry - ENVER, NECATİ (MOSBY-ELSEVIER, 2021)
Objective. Laryngeal framework surgery has been a topic of interest since last decades. To succeed with least morbidity, the most important step is mastering the anatomy of larynx. In this study, we aim to show the relation between body height and laryngeal morphometrics that are important during laryngeal framework surgeries. Data Sources. Larynges of 187 fresh cadavers were dissected within 24 hours after death at the Council of Forensic Medicine. Methods. Age, sex, weight, height, and a total of 12 measurements were taken from each cadaver. Results were subgrouped according to gender, age of 45, body height of 165 millimeters (mm), and thyroid cartilage height of 17 mm. These subgroups were compared for each measurement and ratio. Results. A positive correlation was found between body height and thyroid cartilage height (hTC), thyroid cartilage width, vocal fold length, and distance from projection of anterior commissure (pAC) to inferior border of thyroid cartilage (TIB). Male gender, higher body heights, and higher thyroid cartilage heights significantly higher results were obtained. The ratio between pAC-TIB distance to hTC was found to be 0.54 in males and 0.52 in females, and this ratio was not statistically different in subgroups. Conclusion. Although all of the laryngeal measurements were found to be statistically significant in patients with higher body height, the ratio between pAC-TIB distance to hTC was independent. Thus, especially in patients with body heights longer than average, it should be safer to use the midpoint of the thyroid cartilage as a landmark for anterior commissure.
Keywords: Laryngology; Framework surgery; Cadaver study; Voice; Dysphonia